Analisis Kelayakan Usaha Peternakan Ayam Pedaging (Gallus-gallus domesticus) Di Desa Mangkauk Kecamatan Pengaron Kabupaten Banjar Provinsi Kalimantan Selatan - Wasdiyanta; Baparki, Ahmad; Minta Wahyuningsih, Yayuk (Fakultas Pertanian UVAYA Banjarmasin, 2023)
The background of this research is the existence of business opportunities with the aim of knowing technically the broiler farming business and financially to find out the costs, revenues, income, profits and feasibility of the broiler farming business, taking respondents using the census method and the result is a cost of Rp. 38,368,819.4. , total receipts Rp. 64,156,000.00 and profit of Rp. 25,543,361.2 / production with an RCR value for the broiler farming business of 1.66, which means that this business is worth running at an additional cost of Rp. 1 will increase the profit by Rp. 1.66